2017
DOI: 10.2135/cropsci2017.05.0307
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Constitution and Relationship in Urochloa (Poaceae) Species and Hybrids

Abstract: Urochloa P. Beauv. [syn. Brachiaria (Trin.) Griseb.] belongs to the family Poaceae and comprises species presenting different ploidy levels and modes of reproduction. Specific studies on genomic constitution and relationship within the genus Urochloa are limited, despite the great economic and agronomic importance of forage species and the high frequency of polyploids. Therefore, molecular cytogenetic analyses can enhance the knowledge about genomes and their differentiation, which allows making inferences abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…These studies have revealed several abnormalities typical of allopolyploids and segmental allopolyploids, such as asynchronous chromosome segregation, intragenomic pairing, and the presence of multivalents and micronuclei. More recently, de Paula et al (2017) confirmed the allopolyploidy of U. decumbens 4x and U. brizanth a 4x and Corrêa et al (2020) observed that the diploid genotypes of these species are potential ancestors of allotetraploids. Both studies were performed via genomic in situ hybridization (GISH).…”
Section: Genomic Tools and Resourcesmentioning
confidence: 71%
See 2 more Smart Citations
“…These studies have revealed several abnormalities typical of allopolyploids and segmental allopolyploids, such as asynchronous chromosome segregation, intragenomic pairing, and the presence of multivalents and micronuclei. More recently, de Paula et al (2017) confirmed the allopolyploidy of U. decumbens 4x and U. brizanth a 4x and Corrêa et al (2020) observed that the diploid genotypes of these species are potential ancestors of allotetraploids. Both studies were performed via genomic in situ hybridization (GISH).…”
Section: Genomic Tools and Resourcesmentioning
confidence: 71%
“…Based on genomic in situ hybridization, de Paula et al (2017) recently suggested the allopolyploid origin of U. brizantha and U. decumbens , and such results were validated by additional GISH analysis ( Corrêa et al, 2020 ). The authors proposed genomic compositions of BBB 1 B 1 for U. brizantha , B 1 B 1 B 2 B 2 for U. decumbens , and B 2 B 2 for the diploid U. ruziziensis .…”
Section: Polyploid and Apomixismentioning
confidence: 94%
See 1 more Smart Citation
“…Genome-wide association studies for U. brizantha and U. decumbens are even harder due to the species being segmental allotetraploids, one with genome allotetraploid behavior and the other with autotetraploid behavior (Worthington et al, 2016;de Paula et al, 2017). These species have chromosomes with preferential pairing and fully homologous chromosomes pairing at random (Sybenga, 1996).…”
mentioning
confidence: 99%
“…In this case, genomic studies can be performed using markers with diploid and tetraploid allele dosage. The genomic constitution of U. ruziziensis, U. decumbens, and U. brizantha is classified as B 2 B 2 , B 1 B 1 B 2 B 2 , and BBB 1 B 1 , respectively (de Paula et al, 2017). However, although these genomes have been considered homeologous, less affinity is observed between genomes B and B 2 , and thus genes segregating as a diploid is possible in hybrids between U. ruziziensis and U. brizantha.…”
mentioning
confidence: 99%